Density Functional Theory and ab Initio Computational Evidence for Nitrosamine Photoperoxides: Hammett Substituent Effects in the Photogeneration of the Nitrooxide Intermediate. (13th July 2018) - Greer, Edyta M.; Kwon, Kitae
Abstract: Little attention has been focused on diradical and zwitterionic photoperoxides formed from nitrosamine compounds. Here, an attempt is made to probe the electronic character of the nitrooxide intermediate formed in photochemical reactions with triplet oxygen ( 3 O2 ). Theoretical studies have been conducted to screen para ‐substituted phenyl nitrosamines. In particular, we find that electron‐withdrawing substituents produce low‐lying triplet nitrooxide diradicals. A clear electronic dependence in the S 0 – T 1 and S 0 – S 1 energy gaps of nitrooxides was found using Hammett plots. Computed geometries show a twisted diradical triplet nitrooxide moiety, which contrasts to the nearly flat singlet zwitterionic ground state nitrooxide moiety; analyses of charges (natural bond order), molecular orbitals (HOMO/LUMO) and spin densities enable these assignments. Calculations predict the former triplet species is photogenerated initially from nitrosamine with O2 . The conversion of the triplet nitrooxide diradical to the singlet ground state is an example where longer‐lived zwitterionic nitrooxide structures become possible. The reaction mechanism is consistent with a zwitterionic ground state nitrooxide playing an important role in the bimolecular oxygen‐transfer reaction with phosphine and phosphite trapping agents as has been observed experimentally. Abstract : A time‐dependent DFT study provides computational evidence for the formation of nitrosamine photoperoxides (nitrooxides). Examination of HOMO/LUMO, NBO charges and spin densities was used to predict that the triplet nitrooxide is a diradical, and the singlet ground state nitrooxide is a zwitterion. Electron withdrawing groups enhance the conversion of the triplet nitrooxides to the singlet ground state, where it is predicted to have a longer lifetime.